Kecenderungan non-suicidal self-injury pada remaja: Bagaimanakah peranan kesepian dan life satisfaction? - Shara Vian Fahira; Dyan Evita Santi; Alifia Ananta (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to determine the relationship between loneliness and life satisfaction with the tendency of non-suicidal self-injury. This study has three hypotheses, which contain: 1) there is a relationship between loneliness and life satisfaction with the tendency of non-suicidal self-injury; 2) there is a positive relationship between loneliness and the tendency of non-suicidal self-injury to adolescents; 3) there is a negative relationship between life satisfaction and the tendency of non-suicidal self-injury. Data collection was carried out for four days by distributing questionnaires on a scale of loneliness, life satisfaction and the tendency of non-suicidal self-injury online to 136 adolescents aged 15-22 years in Surabaya. The data analysis used was multiple regression analysis with the help of SPSS 26. The results of this study indicate 1) There is a relationship between loneliness and life satisfaction with the tendency of non-suicidal self-injury; 2) There is a positive relationship between loneliness and the tendency of non-suicidal self-injury to adolescents. This means that the higher the loneliness, the higher the tendency for non-suicidal self-injury; 3) There is a negative relationship between life satisfaction and the tendency for non-suicidal self-injury. This means that the higher the life satisfaction, the lower the tendency for non-suicidal self-injury. Therefore, all hypotheses in this study are accepted. Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara kesepian dan life satisfaction dengan kecenderungan non-suicidal self injury. Penelitian ini memiliki tiga hipotesis, yang berisi : 1) terdapat hubungan antara kesepian dan life satisfaction dengan kecenderungan non-suicidal self injury ; 2) terdapat hubungan yang positif antara kesepian dengan kecenderungan non-suicidal self injury terhadap remaja ; 3) terdapat hubungan yang negatif antara life satisfaction dengan kecenderungan non-suicidal self injury. Pengambilan data dilakukan selama empat hari melalui penyebaran kuisioner skala kesepian, life satisfaction dan kecenderungan non-suicidal self injury secara online kepada remaja berusia 15-22 tahun di Surabaya sebanyak 136 responden. Analisis data yang digunakan adalah analisis regresi berganda dengan bantuan SPSS 26. Hasil dari penelitian ini menunjukkan 1) Adanya hubungan hubungan antara kesepian dan life satisfaction dengan kecenderungan non-suicidal self injury ; 2) Adanya hubungan yang positif antara kesepian dengan kecenderungan non-suicidal self injury terhadap remaja. Artinya semakin tinggi kesepian maka semakin tinggi kecenderungan non-suicidal self injury ; 3) Adanya hubungan yang negatif antara life satisfaction dengan kecenderungan non-suicidal self injury. Artinya semakin tinggi life satisfaction maka semakin rendah kecenderungan non-suicidal self injury. Oleh karena itu, semua hipotesis pada penelitian ini diterima.